Lia Brozgal. Absent the Archive. Liverpool UP, 2020. - Aubrey Gabel (Studies in 20th & 21st Century Literature, 2022)
Review of Lia Brozgal. Absent the Archive. Liverpool UP, 2020. 368 pp.
Keywords: October 17; 1961; Algerian War; cultural studies